2023
DOI: 10.3390/plants12030519
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Autophagy Increases Cell Death in HeLa Cells through Usnic Acid Isolated from Lichens

Abstract: The Western Ghats, India, is a hotspot for lichen diversity. However, the pharmacological importance of lichen-associated metabolites remains untapped. This study aimed to evaluate the cytotoxic potential of lichens of this region. For this, sixteen macrolichens were collected and identified from two locations in the Western Ghats. The acetone extract of Usnea cornuta (UC2A) showed significant cytotoxicity towards multiple human cancer cell lines. Interestingly, co-treatment with chloroquine (CQ), an autophagy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…It has been recently shown that insulin secretion deficiency in beta cells causes ER-stress-mediated cell death [119]. While inhibition of autophagy increases cell death [120,121], rapamycin (an mTOR inhibitor) treatment induced autophagy-promoted cell survival [107,122]. In Kapuy's lab, various natural agents (such as resveratrol, EGCG, sulforaphane) have been successfully used in recent years to delay apoptotic cell death by autophagy induction with respect to excessive levels of ER stress [76,108,123].…”
Section: Autophagy Always Precedes Apoptosis Upon Er Stressmentioning
confidence: 99%
“…It has been recently shown that insulin secretion deficiency in beta cells causes ER-stress-mediated cell death [119]. While inhibition of autophagy increases cell death [120,121], rapamycin (an mTOR inhibitor) treatment induced autophagy-promoted cell survival [107,122]. In Kapuy's lab, various natural agents (such as resveratrol, EGCG, sulforaphane) have been successfully used in recent years to delay apoptotic cell death by autophagy induction with respect to excessive levels of ER stress [76,108,123].…”
Section: Autophagy Always Precedes Apoptosis Upon Er Stressmentioning
confidence: 99%